2012
DOI: 10.1111/j.1755-3768.2012.02457.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐year results of visual outcome with disease activity–guided ranibizumab algorithm for the treatment of exudative age‐related macular degeneration

Abstract: . Purpose:  To evaluate 3‐year follow‐up treatment outcomes with ranibizumab (Lucentis®) 0.5 mg administered either monthly or quarterly on a pro re nata (PRN) basis according to a disease activity–guided monitoring and treatment algorithm. Methods:  A total of 316 treatment‐naive eyes of 316 patients with exudative age‐related macular degeneration met the criteria for inclusion in this retrospective, interventional case series. Patients were treated with ranibizumab 0.5 mg according to a disease activity–guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 14 publications
1
22
0
3
Order By: Relevance
“…Although substantial differences in efficacy could be seen compared to the clinical trials, the results from other observational studies on ranibizumab efficacy were in general similar to the current study (Dadgostar et al 2009;Rothenbuehler et al 2009;Querques et al 2010;Rotsos et al 2010;Gerding et al 2011;Gupta et al 2011;Cohen et al 2013;Finger et al 2013;Lala et al 2013;Rakic et al 2013;Wolf & Kampik 2014). Considering the treatment patterns, an apparent increase in long-term visual acuity was found in patients who completed the loading phase compared to a decrease in visual acuity in those who did not.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Although substantial differences in efficacy could be seen compared to the clinical trials, the results from other observational studies on ranibizumab efficacy were in general similar to the current study (Dadgostar et al 2009;Rothenbuehler et al 2009;Querques et al 2010;Rotsos et al 2010;Gerding et al 2011;Gupta et al 2011;Cohen et al 2013;Finger et al 2013;Lala et al 2013;Rakic et al 2013;Wolf & Kampik 2014). Considering the treatment patterns, an apparent increase in long-term visual acuity was found in patients who completed the loading phase compared to a decrease in visual acuity in those who did not.…”
Section: Discussionsupporting
confidence: 63%
“…Visual acuity gains in previous observational studies after 1 year ranged between 1 and 8 letters on ETDRS chart depending on which treatment regimen was applied. Studies including monthly monitoring showed the better visual acuity results of 7 to 8 letter gains after 1 year (Rothenbuehler et al 2009;Querques et al 2010;Lala et al 2013). In our study, monthly monitoring visits were not mandated, and although part of the prescribing information, this was left to the treating physician's discretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modified PRN strategies or algorithms for retreatments have also been proposed, e.g. 3 systematic monthly intravitreal injections in case of neovascular activity (reinforced PRN) or systematic reinjection every 3 months in the absence of neovascular activity (capped PRN) [17,18]. However, all the PRN strategies require monthly examinations with visual acuity testing, fundus examination or photography, and OCT, which is a burden for patients and physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, actual treatment is based on a pro re nata (as needed) approach (VA, clinical examination, and imaging criteria)98 or treat and extend approach99 with a gradually extending interval of injections depending on fluid recurrence rate. Long-term data on alternative regimen administration protocol are encouraging with an improvement in VA and decrease to five injections per year based on in between protocol (pro re nata and extend)100 or only a small decline of VA after 2 years when compared with monthly injections 101…”
Section: Long-term Efficacymentioning
confidence: 99%